Process optimization of vacuum fried saba (Musa balbisiana) banana chips using response surface methodology - Caincol, Desiree H.; Rustia, Abigail S. (Quezon City College of Home Economics, University of the Philippines Diliman, 2018.)
The aim of the study was to optimize the process parameters for the vacuum frying of saba (Musa balbasiana) banana chips using response surface methodology (RSM). Specifically, the study (1) evaluated the effects of frying time (min), frying temperature (°C), and loading capacity (%) as processing parameters on the quality of vacuum fried saba banana chips; and (2) established and validated the optimum process parameters for the vacuum frying of saba banana chips. Statistical analyses showed that the processing parameters had significant (p<0.05) linear effects on color L* and a* values, two-factor interaction effects on moisture content and color acceptability. Optimum vacuum frying conditions were found to be 7.00 min at 93.09oC with 30.00% loading capacity. This combination of process parameters resulted to saba banana chips with desirable quality attributes in terms of color L* and a* values, moisture content (% dry basis), and color acceptability. Further verification experiments found out that statistical models were accurate in predicting the responses in this study. Results showed that these optimum processing conditions should used to procedure the best quality saba banana chips under a fixed vacuum pressure of 6.0 kPa using the Department of Science and Technology (DOST) -High impact Technology Solutions (HITS) vacuum fryer. The study intended to benefit the saba banana producers in the country as well as the micro, small, and medium enterprises (MSMEs). The product has the potential of becoming a healthier alternative to fried snacks and acooking ingredient.
submitted June 2018
Thesis (B.S. Food Technology)--University of the Philippines Diliman.
Keywords: Saba; Banana chips